CONCEPT OF RISK ASSESSMENT FOR ESTONIAN OIL SHALE MINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper deals with the risk assessment problems in Estonian oil shale mines, where the roomand-pillar mining with blasting is used. This study addresses risks associated with the collapse of mining blocks, including environmental problems. Some of the various factors, which are relevant to Estonian oil shale mines, are determined. For risk estimation the event tree is used. Investigation showed that the likelihood and the consequences of the risk are not acceptable. Risk mitigation process reduces the likelihood. The used concept of risk assessment method is applicable for Estonian oil shale mines. It may be used for different purposes and levels. The results of the risk assessment are of particular interest for practical purposes.